The Influence of Self Integrity and Support from Department/Study Program Management on Students' Willingness to Report Academic Fraud - Niken Utami Kamesa; Sriwidharmanely Sriwidharmanely (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study examined the influence of self integrity and support from department/program study management on students' willingness to report academic fraud. The research method uses a survey method, and data collection is done by distributing online questionnaires via Google Forms. The sample of this study consisted of active students in universities and degree programs, using random sampling as the sampling technique. This study uses the Theory of Planned Behavior (TPB) to measure student behaviour in reporting cheating caused by self integrity and management support at the Department/Study Program—hypothesis testing using moderated regression analysis. Research results show that self integrity has a significant relationship in determining student attitudes toward reporting academic fraud, with additional support from faculty administrators/programs as a moderating variable to strengthen students' desire to report fraud. Students with high levels of self integrity are more likely to report fraud.